Multistage Switching Architectures for Software Routers. - Bianco, A.
Software routers based on personal computer (PC) architectures are becoming an important alternative to proprietary and expensive network devices. However, software routers suffer from many limitations of the PC architecture, including, among others, limited bus and central processing unit (CPU) bandwidth, high memory access latency, limited scalability in terms of number of network interface cards, and lack of resilience mechanisms. Multistage PC-based architectures can be an interesting alternative since they permit us to i) increase the performance of single- software routers, ii) scale router size, iii) distribute packet-manipulation and control functionality, iv) recover from single-component failures, and v) incrementally upgrade router performance. We propose a specific multistage architecture, exploiting PC-based routers as switching elements, to build a high-speed, large-size, scalable, and reliable software router. A small-scale prototype of the multistage router is currently up and running in our labs, and performance evaluation is under way.
Keywords: Central processing unit bandwidth; High memory access latency; Multistage switching architectures; Network devices; Network interface cards; Packet manipulation; Personal computer architectures; Scale router size; Single component failures; Software routers